Structural Evaluation of Bouguer Gravity Data Covering Parts of Southern Niger Delta, Nigeria - , C. C. Ofoha, G. Emujakporue, A. S. Ekine (Archives of Current Research International, 2018)
Qualitative and quantitative methods of data analysis and interpretation were employed on the bouguer gravity data obtained from the Nigerian Geological Survey Agency (NGSA) in Geo soft grid file format. The datasets cover Degema and Oloibiri area of southern Niger Delta. The study is aimed at evaluating those structures that could serve as conduits and entrapments for hydrocarbon and other earth resources like water and minerals. Regional-Residual separation was applied on the bouguer gravity data by means of polynomial fitting of degree one. This art gave rise to the residual and regional maps. Further filtering actions like the first vertical and horizontal derivatives and the second vertical and horizontal derivatives were applied on the residual data in order to accentuate the subtlest anomalies peculiar with the study area. The qualitative analysis and interpretation of the data expressed in grids reveal ENE-WSW, N-S, E-W and WNW- ESE structural features. These trends are regarded as the litho-tectonic domains. Spectral depth analysis was carried on the residual by dividing the residual into overlapping windows. The analysis revealed two depth quantitative models, D1 and D2. D1 represents depths within the basement and its environs while the D2 is associated with shallow related gravity sources. D1 varies from 6.5 km to 21.09 km with an average value of 12.56 km. Conversely, D2 obtained from the less steep section of the energy curve varies between 3.15 km and 7.19 km with an average value of 4.35 km. The average or true sedimentary thickness of 12.56 km suggests that the area will be plausible for hydrocarbon exploration.